4s-10=6s

Simple and best practice solution for 4s-10=6s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4s-10=6s equation:


Simplifying
4s + -10 = 6s

Reorder the terms:
-10 + 4s = 6s

Solving
-10 + 4s = 6s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-6s' to each side of the equation.
-10 + 4s + -6s = 6s + -6s

Combine like terms: 4s + -6s = -2s
-10 + -2s = 6s + -6s

Combine like terms: 6s + -6s = 0
-10 + -2s = 0

Add '10' to each side of the equation.
-10 + 10 + -2s = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -2s = 0 + 10
-2s = 0 + 10

Combine like terms: 0 + 10 = 10
-2s = 10

Divide each side by '-2'.
s = -5

Simplifying
s = -5

See similar equations:

| 4(5x+2)=Y | | 10-3u=-5u-4 | | 4(x-1)+2x=6(x-6) | | 4s+7t=79 | | -8g=-9g+3 | | p=-5+2p | | 2(5)+3(0)= | | 6x+2x+x+3=39 | | -f=9f+10 | | x^2+2x+y^2+14y-5=0 | | -3(2h-8)=-32-7h | | 6x+10=-3x+109 | | 1-6d=-5d | | 4k=-6 | | 3s+2t=30 | | 4b+6=7b | | -2k+9=-k | | 10x+4=-34 | | x+5=5x+6 | | 4(9-6)+4=2a-6 | | -0.4x+0.5x-9=5 | | -3f=-4f+9 | | 7x+5=-x+5 | | 3n-7(n+3)=7 | | 2[4+x]=-16 | | (4)-(-1)= | | 6u=5u-6 | | -89.0602=10.861b | | 16=8m | | 20x^3+24x^2+4x=0 | | -104=10-6w | | 3(7m+5)+4(3m-8)=148 |

Equations solver categories